2003
DOI: 10.1002/pa.139
|View full text |Cite
|
Sign up to set email alerts
|

Marketing political soap: a political marketing view of selling candidates like soap, of electioneering as a ritual, and of electoral military analogies

Abstract: This paper examines three common political expressions and ideas from a marketing perspective. First, the origins of the ‘selling candidates like soap’ expression are traced and it is argued that, rather than being ‘sold’ like a product, candidates are instead ‘marketed’ like a service provider such as a real estate agent. Traditional campaign rituals have a legitimate marketing function if electors, and not just political actors, are meaningfully incorporated and military analogies in elections have increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
10

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 22 publications
0
14
0
10
Order By: Relevance
“…A pesquisa acadêmica internacional focaliza não só aspectos utilitários do marketing político através da utilização de ferramentas do marketing tradicional (Niffenegger, 1989), como também existem estudos teóricos que aplicam teorias comportamentais e políticas no estudo do comportamento do eleitor, na análise do evento eleição como um ritual e o uso de analogias militares em campanhas (Marland, 2003). Há também os que buscam uma teoria específica do marketing político (Wring, 1997), como também aqueles que buscam evidenciar e comparar as semelhanças e diferenças entre o marketing tradicional e o político (Kotler, 1975;Shama, 1975;Lock e Harris, 1996).…”
Section: Referencial Teóricounclassified
See 2 more Smart Citations
“…A pesquisa acadêmica internacional focaliza não só aspectos utilitários do marketing político através da utilização de ferramentas do marketing tradicional (Niffenegger, 1989), como também existem estudos teóricos que aplicam teorias comportamentais e políticas no estudo do comportamento do eleitor, na análise do evento eleição como um ritual e o uso de analogias militares em campanhas (Marland, 2003). Há também os que buscam uma teoria específica do marketing político (Wring, 1997), como também aqueles que buscam evidenciar e comparar as semelhanças e diferenças entre o marketing tradicional e o político (Kotler, 1975;Shama, 1975;Lock e Harris, 1996).…”
Section: Referencial Teóricounclassified
“…Mas essa ana logia pode esconder algumas diferenças mais explicativas do que as semelhanças que existem entre o marketing comercial e o político. O marketing político é sistematicamente comparado com o marketing comercial, seja através de seus conceitos e ferramentas, seja por meio dos modelos de comportamento do consumidor (Kotler, 1975;Shama, 1975;Lock e Harris, 1996;Marland, 2003;Bannon, 2003).…”
Section: Relação Entre O Marketing Político E De Empresasunclassified
See 1 more Smart Citation
“…Dean and Croft (2001) proposed that political marketing is similar to relationship and internal marketing, where the party has to build a relationship with its supporters and internal staff through marketing concepts. Marland (2003) added a similar point by suggesting that political marketing is more similar to the real-estate industry, due to the heavy human interaction within the service industry in contrast with most other commercial sectors. These researchers did not compare how audiences consume political or commercial mediated messages, but in general they concluded that voters and consumers have more differences than similarities.…”
Section: Introductionmentioning
confidence: 99%
“…Dans une ère de politique médiatisée et de marketing politique, le cliché, a priori séduisant, selon lequel « les candidats sont commercialisés comme l'est le savon 3 » ne peut s'évacuer aisément. Bien que la notion simpliste du « candidat équivalent à un savon » ait profondément été mise en question par des chercheurs en communication et par des politologues (Marland 2003), il est admis que « l'apparence et la manière de parler d'un candidat ont un impact considérable sur les chances d'élection de ce même candidat » (Rosenberg et al 1986 : 108). Pour les besoins de cet article, considérons la définition donnée par Kenneth L. Hacker du terme « image du candidat » comme étant une « accumulation des perceptions des électeurs sur les candidats » (2004 : 4).…”
unclassified